The Dynamics of Stock Prices and Exchange Rate: Evidence from Nigeria (2012)
This paper probed the long-run and short-run dynamics between stock prices and exchange rates in Nigeria using the Johansen and Gregory-Hansen cointegration analyses, causality test and Exponentional General Autoregressive Conditional Heteroskedasticity modeling on daily data from January 2, 2002 to August 11, 2011.The results showed that there is no long run relationship between stock prices and exchange rate in Nigeria, albeit, with a structural break date of mid April 2007, which coincides with the period when the stock prices plumped precipitously from the impact of global financial crisis in early 2007. In addition, the results indicated that there is a unidirectional relationship from stock prices to exchange rate and that the EGARCH modeling suggested that a 100% increase in stock prices would lead to a 1.66% appreciation of the exchange rate. Thus, it is imperative for monetary authorities in Nigeria to take into account the role of stock market development in the conduct of its exchange rate policy.